Calculation procedures to estimate fine root production rates in forests using two-dimensional fine root data obtained by the net sheet method. (8th May 2017) - Noguchi, Kyotaro; Tanikawa, Toko; Inagaki, Yoshiyuki; Ishizuka, Shigehiro
Abstract: Several recent studies have used the net sheet method to estimate fine root production rates in forest ecosystems, wherein net sheets are inserted into the soil and fine roots growing through them are observed. Although this method has advantages in terms of its easy handling and low cost, there are uncertainties in the estimates per unit soil volume or unit stand area, because the net sheet is a two-dimensional material. Therefore, this study aimed to establish calculation procedures for estimating fine root production rates from two-dimensional fine root data on net sheets. This study was conducted in a hinoki cypress ( Chamaecyparis obtusa (Sieb. & Zucc.) Endl.) stand in western Japan. We estimated fine root production rates in length and volume from the number (RN) and cross-sectional area (RCSA) densities, respectively, for fine roots crossing the net sheets, which were then converted to dry mass values. For these calculations, we used empirical regression equations or theoretical equations between the RN or RCSA densities on the vertical walls of soil pits and fine root densities in length or volume, respectively, in the soil, wherein the theoretical equations assumed random orientation of the growing fine roots. The estimates of mean fine root (diameter <1 mm) production rates were ∼80–100 g m −2 year −1 using the empirically obtained regression equations, whereas those from the theoretical equations were ∼40–50 g m −2 year −1 . The difference in the estimates was attributed to larger slope values of the empirical regression equations than those of the theoretical equations, suggesting that fine root orientation was not random in our study site. In light of these results, we concluded that fine root production rates were successfully estimated from two-dimensional fine root data on the net sheets using these calculation procedures, with the empirical regression equations reflecting fine root orientation in the study site.